Tactical Planning Model for Procurement and Manufacturing Decisions under Environmental Regulations. Issue 3 (2015) - Trochu, Julien; Chaabane, Amin; Ouhimmou, Mustapha
Abstract: In this paper, we study the problem of procurement and manufacturing planning under environmental regulations. This work introduces an integer linear programming model (ILP) considering supply chain purchasing and manufacturing tactical decisions under the compensation regulation. The proposed model allows the use of clean production technologies to manufacture one product family based on two versions of bill of materials (BOM): standard and green. As the compensation regulation penalizes companies for the excessive weight of products sold on the market, this green version with lighter BOM is used to demonstrate the impact of this new regulation on the total supply chain cost for companies operating in the province of Quebec. The results may yield cost reduction through the development of eco designed products and the use of clean technologies. In this case, the compensation decreases significantly and the company remains competitive.